Metabolomic Profile of the Fungus Cryomyces antarcticus Under Simulated Martian and Space Conditions as Support for Life-Detection Missions on Mars - Gevi, Federica; Leo, Patrick; Cassaro, Alessia; Pacelli, Claudia; de Vera, Jean-Pierre Paul; Rabbow, Elke; Timperio, Anna Maria; Onofri, Silvano (Frontiers in Microbiology, 2022)
The identification of traces of life beyond Earth (e.g. Mars, icy moons) is a challenging task because terrestrial chemical-based molecules may be destroyed by the harsh conditions experienced on extraterrestrial planetary surfaces. For this reason, studying the effects on biomolecules of extremophilic microorganisms through astrobiological ground-based space simulation experiments is significant to support the interpretation of the data that will be gained and collected during the ongoing and future space exploration missions. Here, the stability of the biomolecules of the cryptoendolithic black fungus Cryomyces antarcticus, grown on two Martian regolith analogues and on Antarctic sandstone, were analyzed through a metabolomic approach, after exposure to Science Verification Tests (SVTs) performed in the frame of the European Space Agency (ESA) BIOMEX (Biology and Mars EXperiment) project. These tests are building a set of ground-based experiments performed before the space exposure aboard the International Space Station (ISS). The analysis aimed to investigate the effects of different mineral mixtures on fungal colonies and the stability of the biomolecules synthetized by the fungus under simulated Martian and space conditions. The identification of a specific group of molecules showing good stability after the treatments allows to create a molecular database which should support the analysis of future data sets that will be collected in the ongoing and next space exploration missions.